Quantification of Operative Actions in Obstetric and Gynecological Cases at Premagana Hospital in 2021-2022 - Bayuningrat, I Gusti Ngurah Made; Pradnyaningrat, I Gusti Ngurah Andika Manik; Dwinanta Kartha, Ida Bagus Bramantya (Fakultas Ilmu Kesehatan, 2023)
Surgery or operative procedures are invasive actions performed to diagnose, treat diseases, injuries, or body deformities, typically involving incisions that can cause physiological changes in the body and affect other organs. Operative procedures, including in obstetrics and gynecology cases, are frequently performed as part of therapy modalities and for diagnostic purposes. The research problem focuses on the types and number of operative procedures in obstetrics and gynecology cases at RSU. Premaganain Gianyar Regency, as there has been a lack of data and research on the prevalence of such procedures. The aim of this study is to provide an overview of various types and numbers of operative procedures in obstetrics and gynecology cases at RSU. Premaganain 2021-2022. This research is a descriptive study of operative procedures in obstetrics and gynecology cases using a cross-sectional design approach. Method: Secondary data collection from medical records of operative procedures in obstetrics and gynecology cases at RSU. Premaganain 2021-2022, followed by tabulation, recapitulation, and quantification of the types and numbers. Results: Operative procedures in obstetrics and gynecology cases at RSU. Premaganain 2021-2022 include Cesarean section (CS), Cesarean section with Operative Method for Women (CS-OWM), Total Abdominal Hysterectomy (TAH), Supra Vaginal Hysterectomy (SVH), Total Vaginal Hysterectomy (TVH), Cystectomy, Salpingectomy, Salpingo-oophorectomy, Dilatation and Curettage (D&C). The dominant operative procedure in obstetrics cases is CS at 82-83%, while in gynecology cases, it is Total Abdominal Hysterectomy (TAH) at 1.3-2.2%.